Islamicity Performance Index Dan Islamic Social Reporting Terhadap Kinerja Perbankan Syariah Di Indonesia Pasca Covid-19 - Cahaya Fitriana Dewi Amala; Malihatin; Citra Amanda; Ely Windarti Hastuti (Universitas Muhammadiyah Malang, 2022)
Islamic banking is an institution that works to carry out company activities in accordance with sharia principles. Islamic banking needs to measure financial performance in the post-covid-19 period. The ratios that can be used to measure financial performance are Islamicity Performance Index and Islamic Social Reporting. This study aims to analyze the effect of the Islamicity Performance Index and Islamic Social Reporting on the financial performance of Islamic banking in Indonesia after COVID-19. This type of research is quantitative. The sample used is in 2020-2021 totaling 11 samples. The data analysis technique used is panel data regression analysis which is processed using the Eviews 12 program. The results of this study indicate that the Islamicity Performance Index and Islamic Social Reporting shows that there is a significant effect on Financial Performance.